[BP.09.03] ASSOCIATION OF CIRCULATING OSTEOPROTEGERIN (OPG) AND RANKL WITH INTRACRANIAL ARTERIAL CALCIFICATION IN HYPERTENSIVE PATIENTS. (September 2017) - Cheng, Y.; Wang, Y.; Guo, Q.; Zhu, D.; Li, Y.
Abstract : Objective: The axis of osteoprotegerin (OPG), the receptor activator for nuclear factor κB (RANK), and RANK ligand (RANKL) has been reported to be critical regulators of skeletal biology and calcification process. However, data was scarce on its involvement in intracranial arterial calcification. Design and method: Hypertensive patients with at least two cardiovascular risk factors were recruited from Shanghai Xinzhuang Community. Plasma OPG (Lifespan, Seattle, WA) and serum RANKL (Biomedica, Vienna, Austria) were measured with commercialized ELISA kits and log-transformed for analysis. Brain tomographic angiography (CTA) was performed with a GE FX/I helical CT scanner (General Electric, United States). The Hounsfield density was measured using a pixel lens on the CTA images. Calcification was defined as a focal high-density lesion of at least 120 Hounsfield units at the intracranial arteries. Pearson's correlation, single and multiple logistic regressions were applied for analysis. Results: The 831 patients (mean age, 65 years; 54% women) included 465 (56%) with intracranial arterial calcification. Mean clinic blood pressure was 137/72 mmHg and 736 (89%) patients were on anti-hypertensive treatment. Plasma OPG, but not serum RANKL, showed seasonal variation (P < 0.001), 15.6% higher (P < 0.001) in summer and 6.0% lower (P < 0.001) in autumn, relative to the mean level in the whole year. Plasma OPG was negatively associated with RANKL (r = −0.25; P < 0.001). The prevalence of intracranial arterial calcification increased with plasma OPG (49.1%, 56.8% and 61.9% in tertiles 1, 2, and 3, respectively; P = 0.003) and decreased with serum RANKL (61.6%, 54.8% and 49.2% in tertiles 1, 2, and 3, respectively; P = 0.005). In continuous analyses, RANKL, but not OPG (P = 0.57), remained significantly associated with intracranial arterial calcification after adjustment (OR [95%CL] associated with 1-SD increase: 0.63 [0.41, 0.99], P = 0.043). RANKL increased by 14.7% with total/HDL cholesterol ratio (P < 0.001), and decreased by 6.9% with neutrophils/lymphocyte ratio (P = 0.02). In pathway analysis, total/HDL cholesterol ratio had both a direct (P = 0.002) and RANKL-mediate indirect (P = 0.008) effect on intracranial arterial calcification. Conclusions: Circulating RANKL was associated with intracranial arterial calcification, highlighting that it might be a marker of intracranial arterial calcification. Further research is warranted to understand the precise mechanisms underpinning this association.